Drainage trench conductivity and biogenic materials retention - Klimašauskas, Mindaugas; Šaulys, Valentinas (International Conference “Environmental Engineering”, 2017)
In the work, the effectiveness of hydrosystem functioning, when the filtration characteristics of the drainage trench backfill are improved by admixing lime materials, is analysed after a 28 ear period of use. The tests of effectiveness of hydrosystem functioning were carried out in the test object of Raseiniai district, Kalnujai. The drainage was installed in the drying systems and the filtration characteristics of trench backfills were improved by admixing the lime material. Analysing the maximum comparative debits of drainage in the control drying systems in the period of spring and autumn 2016 (0.006 and 0.190 ml/s m, respectively) as well as comparative debits in the period of spring and autumn (0.015 and 0.311 ml/s m, respectively) in the drainage, which filtration characteristics of trench backfills were improved by admixing chalkly materials (0,6% ground mass), the results were better by 60.0 and 38.9%, respectively. Assessing the drainage system effectiveness indexes of 2012, 2013 and 2016 with the reliability of 95%, it can be stated that the effectiveness of drainage functioning, when the lime materials were used for the improvement of the filtration characteristics of drainage, did not change essentially after a 28 ear period of use.
Keywords: drainage; drainage trench conductivity; drainage renovation